Role of sudden application or withdrawal of magnetic field on MHD couette flow - Jha, Basant K.; Oni, Michael O. (Zielona Góra: Uniwersytet Zielonogórski)
This article investigates the impact of a sudden application or sudden withdrawal of a magnetic field on an unsteady MHD Couette flow formation in a parallel plate channel. The governing momentum equation is derived and solved exactly in Laplace domain using the Laplace transform technique with the necessary initial and boundary conditions to capture the present physical situation for the cases; sudden application or sudden withdrawal of a magnetic field.
Keywords: MHD; Couette motion; Riemann-Sum approximation technique; Hartmann number; parallel plates